2016
DOI: 10.1021/acs.cgd.6b01566
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization from the Amorphous State of a Pharmaceutical Compound: Impact of Chirality and Chemical Purity

Abstract: The crystallization behavior and morphological features of particles obtained from amorphous diprophylline (DPL) are reported. After fast cooling of the melt, progressive heating above the glass transition (T g ≈ 37 °C) induces the nucleation and growth of well-shaped crystals: PC for primary crystals. The combination of differential scanning calorimetry, hot stage optical microscopy, powder X-ray diffraction, and Raman spectroscopy revealed that these PC are kinetically favored and can form spontaneously in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…3It was demonstrated that, (Coquerel and Tamura, 2016). Many experimental confirmations have been reported in literature: limonene (Gallis et al, 2000), diprophylline (Viel et al, 2017) or ibuprofen (Kim et al, 2014). For the same cooling or heating conditions, Tg value was not impacted by the asymmetric property of chirality.…”
Section: Thermal Lag and Glass Transitionmentioning
confidence: 74%
See 1 more Smart Citation
“…3It was demonstrated that, (Coquerel and Tamura, 2016). Many experimental confirmations have been reported in literature: limonene (Gallis et al, 2000), diprophylline (Viel et al, 2017) or ibuprofen (Kim et al, 2014). For the same cooling or heating conditions, Tg value was not impacted by the asymmetric property of chirality.…”
Section: Thermal Lag and Glass Transitionmentioning
confidence: 74%
“…For numerous set of organic compounds (e.g. alkylamide derived from trans-1,2-bis(amino)cyclohexane, diprophylline), racemic mixture has a much higher propensity to crystallize compared to the enantiomeric counterpart (Coquerel and Tamura, 2016;Viel et al, 2017). It is important to notice that the racemic mixtures studied in the mentioned works crystallize as racemic compounds (i.e.…”
Section: Impact Of Enantiomeric Composition On Gfa and Crystallizationmentioning
confidence: 99%
“…Higher Gibbs free energy of amorphous drugs than crystalline drugs let them to have higher solubility (70). However amorphous materials are unstable (71). Therefore amorphous form of drugs is incorporated into polymer matrixes due to formation of solid dispersion (72).…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…Systematic studies on the amorphous state of molecular compounds with a stereogenic chiral center are largely available in the literature [15][16][17][18][19][20][21][22][23][24][25] . A recent and increasing interest is paid to the investigation of chirality influence in molecular amorphous systems regarding their molecular mobility [26][27][28][29] , their glass forming ability 30 and their crystallization behavior 26,28,[31][32][33] as function of the initial enantiomeric composition. From these studies, it is clear that the glass transition temperature Tg appears to be independent of the enantiomeric excess (ee: the absolute difference between the mole fractions of each enantiomer (ee = 0% racemic composition, ee = 100% pure enantiomer) 7,[26][27][28]32,33 , same for the characteristic size of cooperative movements and relaxation landscape 28,33 .…”
Section: Introductionmentioning
confidence: 99%